Acquiring Satellitar Data and Post-Processing Digital Model to Analyze Geophysic Morphology of (Submerged) Landscape - Virtual Geomorphological Model of a Submerged Canyon off Southeast Sicily - Giuseppe Avola (Annals of Limnology and Oceanography - Peertechz Publications, 2016)
The central area of the Mediterranean Sea is characterized by the bathymetric conformation of its seabed and especially for having been subjected, like other waters in the world, to transformations dependent on the change in sea level that caused the submergence at different stages and during the glacial and post-glacial periods, the emergence. Through the consideration of the geological phenomena that have altered the morphology of the landscape in the Sicilian Channel, during glacial and interglacial phase, will be analyze the underwater topography of the great geological plateau combining tectonically Malta and Sicily, especially the eastern side, which gradually slopes down to the high depth of the central Mediterranean basin.